USING ICT TO SUPPORT STUDENTS WITH DYSLEXIA - Khalid Mohammed Almahrag (Human Research in Rehabilitation, 2022)
Dyslexic students often have the excellent joint capability, yet many fail to get the mastery of reading. The signs of dyslexia may affect many fields of learning and activities. They may be characterized as a combination of difficulties that influence the learning process in reading, spelling, or writing. It is mainly connected with mastering written language, although spoken language may also be affected. The application of information and communications technology (ICT) is a vital tool to rectify gaps and weaknesses for students who have difficulties spelling and writing and can be highly favorable to dyslexic students. Developing word processing skills allows people with dyslexia, particularly those with scanty motor skills, to better present their work and frees them from the process of writing. Mastering typing and word processing skills are life skills, and the struggle taken up in learning to type will be well recompensed (Beveridge, 1999). In this paper, We will examine the characteristics of dyslexic children and how ICT can facilitate some of their weaknesses and enable them to succeed in taking more control over their learning. We also consider what the advantage and disadvantages to children with dyslexia of using a computer are.